2019
DOI: 10.3889/oamjms.2019.204
|View full text |Cite
|
Sign up to set email alerts
|

The Importance and Extent of Providing Compassionate Nursing Care from The Viewpoint of Patients Hospitalized in Educational Hospitals in Kermanshah - Iran 2017

Abstract: AIM: This study is an attempt to determine the importance and extent of providing compassionate nursing care from the hospitalised patients’ viewpoint in educational hospitals in Kermanshah-Iran 2017 METHODS: The study was carried out as a descriptive, analytical work in the hospitals affiliated to Kermanshah University of Medical Sciences on 300 patients in 2017. The patients were selected through convenient sampling, and Burnell Compassionate Care Scale was filled by the participants. The collected dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…In a study conducted in Ghana, about 72% of the respondents said that maltreatment was the common problem, and 77.4% said private facilities treat their clients more respectfully than public facilities [ 37 ]. Care and compassion in health care delivery were stated in 2 studies on the principles of compassion in health care practices and from the hospitalized patient viewpoint [ 38 , 39 ]. Only 1 study was conducted on compassionate and respectful health care delivery and showed that the magnitude of disrespect was 43% [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in Ghana, about 72% of the respondents said that maltreatment was the common problem, and 77.4% said private facilities treat their clients more respectfully than public facilities [ 37 ]. Care and compassion in health care delivery were stated in 2 studies on the principles of compassion in health care practices and from the hospitalized patient viewpoint [ 38 , 39 ]. Only 1 study was conducted on compassionate and respectful health care delivery and showed that the magnitude of disrespect was 43% [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this review, 14 studies originated from Africa, namely Ethiopia, Ghana, Nigeria, Burkina Faso, and South Africa [ 27 - 29 , 31 , 32 , 34 - 37 , 40 - 43 , 45 ], and 5 studies were from other continents, in the countries of Iran, the United Kingdom, European countries, and China [ 26 , 30 , 33 , 39 , 44 ]. A qualitative approach was used by 10 of the studies [ 28 , 29 , 31 , 33 - 36 , 41 , 43 , 44 ], 2 used a mixed approach [ 27 , 30 ], 5 were cross-sectional studies [ 32 , 37 , 40 , 42 , 45 ], 1 was a descriptive-analytical study [ 39 ], 1 was based on expert consensus [ 26 ], and 1 was an expert review [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nurses can help health community by providing compassionate nursing care (44). One example of this is self-care education for patients(12, 42, 43).…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] The test-retest reliability of the Self-Compassion Scale was evaluated by Neff, and its Cronbach's coefficient alpha was calculated as 0.92. [ 22 ] Odou et al . [ 23 ] reported the internal consistency of the scale as 0.92.…”
Section: Methodsmentioning
confidence: 99%